The Role of Energy Literacy in Supporting Energy Conservation: Perspective from Indonesian Citizens - Laurentius Kevin Hendinata; Tantri Ardiwinata; Filipus Kevin Tirta Pratama (Purnomo Yusgiantoro Center, 2022)
Energy plays a strategic role in human life today. In this case, energy is an interdisciplinary concept from the concepts of science and the environment to global social problems. One aspect of energy development is energy conservation, where efficient and rational use of energy is carried out without reducing energy use performance. To increase public awareness and participation on energy issues, especially those related to energy conservation, it is necessary to increase knowledge about energy in the wider community, one of which is through energy literacy. This is because knowing energy will empower people to make wise decisions and take responsible action regarding energy use. Energy literacy here can be obtained through formal and informal education. This study investigates the condition of energy literacy in Indonesian society in general through a sampling method, and it is found that the level of energy literacy in Indonesian society is on a moderate scale, but it is still not enough to reach the expected level of energy literacy, while the energy literacy level is less. Energy literacy and energy conservation will also be increasingly hampered. Therefore, it is hoped that an increase in education or energy literacy related to formal and non-formal education so that people are more familiar with and apply energy conservation in their daily lives.